PENGARUH CUSTOMER RELATIONSHIP MARKETING, PERSEPSI HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KEJU PROCHIZ PADA PERUSAHAAN PT SINAR MAYURI KLUNGKUNG - Mahendra, I Nyoman Dwi Arysna; Wijayanthi, Ni Putu Ayu Putri (Jurnal MBE Manajemen Bisnis, Equilibrium, 2024)
Understanding customer behavior when it comes to making purchases is a crucial step in business success. It helps companies better comprehend the market, optimize marketing strategies, and maintain a competitive edge. Managing customer relationships, aligning prices with perceived value, and offering high-quality products all contribute to optimizing customer purchases. This study aims to determine the influence of Customer Relationship Marketing, Price Perception, and Product Quality on the Purchase Decision of Prochiz Cheese at PT Sinar Mayuri, as well as to establish which factor dominates in optimizing the purchase decisions of Prochiz Cheese at PT Sinar Mayuri. Sampling was conducted using a saturated sample consisting of 78 respondents. Data collection methods included observation, interviews, literature review, and questionnaires. The data analysis technique used was multiple linear regression analysis. The study's findings indicate that there is a significant partial and simultaneous influence between Customer Relationship Marketing, price perception, and product quality on the purchase decisions of Prochiz Cheese at PT Sinar Mayuri Klungkung.